Risk factors for postoperative acute kidney injury after cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy: a meta-analysis and systematic review - Dengzhuo Chen; Yongli Ma; Jinghui Li; Liang Wen; Linfeng Liu; Guosheng Zhang; Hongkai Hu; Chengzhi Huang; Xueqing Yao (World Journal of Surgical Oncology)
Abstract Background Acute kidney injury after CRS + HIPEC is a serious postoperative complication, but only a few studies have reported its postoperative risk factors. In addition, there are large discrepancies in the results of available observational studies. Methods We searched The Cochrane Library, Embase, Web of Science,and PubMed to identify observational studies reporting risk factors for AKI after CRS + HIPEC. A meta-analysis was performed to investigate the effect of various preoperative and intraoperative risk factors on AKI after CRS + HIPEC. Results A total of 7 studies were included in this study, comprising 1550 patients who developed AKI after CRS + HIPEC. The results of meta-analysis showed that the significant preoperative risk factors were age, sex, BMI, eGFR, Hb, PCI, diabetes mellitus, and hypertension. IO cisplatin, IO SBP < 100 was identified as an intraoperative risk factor, whereas IO mitomycin emerged as a protective factor for postoperative AKI. In addition, the risk of postoperative AKI varied by primary tumor site, with Appendix being less prone to AKI, while mesothelioma and ovarian, two sites with a greatly elevated risk of postoperative AKI. Conclusions This meta-analysis identified a number of risk factors for postoperative AKI after CRS + HIPEC. By identifying these risk factors, it is more beneficial for clinicians to perform early preoperative interventions and select the most appropriate treatment strategy for their patients, thus minimizing the risk of postoperative AKI. Trial registration PROSPERO CRD42024585269.